FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN IBU HAMIL DALAM MENGKONSUMSI TABLET FE DI KECAMATAN MERAL BARAT KABUPATEN KARIMUN TAHUN 2017 - qurnia, mutia; Nurul Aulia, Devy Lestari (Universitas Batam, 2018)
It was documented that the incidence of anemia occured to 37.1% prenatal women in Indonesia. The higher rate moreover happened in Karimun district noted in 2016 reached 49.5% in which 35.1% cases happened in West Meral by Desember 2016. Hence, this study aims to determine the factors influencing the prenatal mothers compliance to take the fe tablet during the pregnancy. This research designed as an analytic survey research of cross sectional study approach. This study was conducted in West Meral dated from May to June 2017. As the population, the researchers took all third-trimester prenatal women, in which from all respondents, 43 respondents was taken as the sample through total sampling technique. The questionnaire was utilized as the research instrument where the data gathered further analyzed by univariate and bivariate Chi-Square statistical test. Based on the analysis, it is resulted 61.5% of prenatal women with good knowledge level routinely took the fe tablet, 58.6% mothers with negative attitude found not to take the fe tablet regularly, and 75% mothers whom did not get family support also not take the fe tablet frequently. These results portray that there no significant correlation of the knowledge level of the prenatal women compliance to their attitude and the family support in taking the fe tablet regularly during the pregnancy period. In the future, it is expected that the family to give their support to the prenatal mothers and also the health personnel to give advices about the important of the fe tablet during the pregnancy for both the mother and the infant.